Opinion of Women in Kafr El-Sheikh Governorate Regarding Prohibition and Criminalization of Female Genital Cutting - Seham Ragheb; Maha El-Habashy; Randa Abd El-khalik (Journal of High Institute of Public Health, 2010)
bjective: The study aimed to identify the opinion of women regarding prohibition and criminalization of female genital cutting (FGC). Methods: The study was conducted at the five medical health centers located in at Kafr El-Sheikh governorate. A total of 250 women attending these centers were selected. Fifty women were selected from each center. An interview schedule was designed and used to collect data. It consists of three parts: the first part included socio-demographic characteristics, the second part entailed the women's knowledge about FGC, and third part contains the details of knowledge about and opinion of women regarding the law that prohibits and criminalizes FGC. Results: The main findings of the study revealed that more than one half (51.2 %) of the study sample were against prohibition and criminalization of FGC and only 27.2 % agreed that it should be prohibited and criminalized, while 3.6 % were uncertain. Mass media was the main source of information about the law, yet, at certain times mass media messages were ambiguous. As a result only one fifth of the sample changed their opinion about FGC during the previous year.